High-responsivity modulation-doped AlGaAs/InGaAs thermopiles for uncooled IR-FPA utilizing integrated HEMT-MEMS technology - Abe, Masayuki (2013)
Novel thermopiles based on modulation-doped AlGaAs/InGaAs heterostructures are proposed and developed for the first time for uncooled IR focal plane array (FPA) image sensor application. The high responsivity R with the high-speed response time τare designed to be 4900 V/W with 110 μs. Based on integrated high-electron-mobility-transistor-microelectromechanical-system technology, the 32 × 32 matrix FPAs are fabricated to demonstrate its enhanced performance by blackbody measurement. The technology presented here demonstrates the potential of this approach for low-cost uncooled IR FPA applications.